META-ANALYSIS: IMPLEMENTATION OF THE PROJECT BASED LEARNING (PJBL) MODEL IN INCREASING STUDENTS' CREATIVE THINKING IN SCIENCE LEARNING - Melisa, Defri; Nawahdani, Ahmad Mansur; Alam, Rezwanul (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research is a qualitative study that uses meta analysis methods. The aim of this meta analysis is to find out whether there is an increase in students' creative thinking in the science learning context after implementing the Project Based Learning model. The data collection process was carried out by searching for journals that had been published in national journals using the Google Scholar platform. The ten journal articles analyzed came from publications in the last three years, namely the 2021-2023 period. This research process involves data collection steps, followed by data analysis. The analytical method used is qualitative analysis by applying the Miles and Huberman techniques. Based on the results of the meta analysis in this research, it can be concluded that the application of the Project Based Learning learning model is able to improve students' creative thinking in the science context.